(untitled) (Journal of Shaheed Suhrawardy Medical College, 2026)
Background: Gynecological complications during pregnancy remain a major contributor to maternal morbidity and mortality in Bangladesh and other low-resource settings. Understanding the pattern of presenting symptoms, clinical findings, and outcomes is essential for improving obstetric care. Objectives: This study aimed to assess the pattern of gynecological problems among pregnant women attending a tertiary care hospital in Bangladesh, focusing on demographic distribution, common clinical presentations, management approaches, and maternal outcomes. Methods: A cross-sectional observational study was conducted over twelve months among 100 pregnant women admitted with gynecological complaints. Data on demographic variables, symptoms, clinical examination findings, management modalities, and maternal outcomes were collected and analyzed. Associations between factors such as age group, parity, gestational age, abdominal tenderness, blood transfusion, and blood pressure with key outcomes were examined using chi-square tests. Results: Abdominal pain (35%) and PV bleeding (22.5%) were the most frequent presenting complaints. Conservative management was provided to 62% of women, while 38% required surgical intervention. Maternal outcomes showed 59% improvement, 39% complications, and 2% mortality. Significant associations were found between gestational age and management type (p < 0.001), blood transfusion and maternal outcome (p < 0.001), and systolic blood pressure and maternal outcome (p = 0.003). Age group was associated with PV bleeding (p = 0.042). Parity and abdominal tenderness showed no significant association with maternal outcomes in this cohort. Conclusion: Gynecological emergencies in pregnancy commonly present with abdominal pain and PV bleeding. Advanced gestational age, high systolic blood pressure, and transfusion requirement strongly predict adverse outcomes, while abdominal tenderness and parity were not significant determinants. Early recognition and targeted management of high-risk clinical indicators are essential to improve maternal outcomes in tertiary care settings. J Shaheed Suhrawardy Med Coll 2024; 16(2): 30-35